Guillain-Barré syndrome temporally associated with COVID-19 vaccines in Victoria, Australia. Issue 52 (12th December 2022) - Osowicki, Joshua; Morgan, Hannah J.; Harris, Adele; Clothier, Hazel J.; Buttery, Jim P.; Kiers, Lynette; Crawford, Nigel W.; ,
Highlights: There have been conflicting reports regarding a temporal association between COVID-19 vaccination and Guillain-Barré Syndrome (GBS). This case series from Victoria, Australia, reports an excess of GBS cases following dose 1 of the adenovirus-vector COVID-19 vaccine Vaxzevria ChadOx1-S (AstraZeneca). Global collaborative studies are required to provide precision and generalizability regarding risks of Adverse Events Following Immunization (AEFI) associated with different vaccine platforms. To support further development of the adenovirus-vector vaccine platform, there is an urgent need for research exploring the mechanisms underlying Adverse Events of Special Interest (AESI) such as GBS, and whether predictive biomarkers may help to minimize risks. Abstract: Guillain–Barré syndrome (GBS) is an adverse event of special interest (AESI) for surveillance systems monitoring adverse events following immunisation (AEFI) with COVID-19 vaccines. Emerging data support a temporal association between GBS and adenovirus-vector COVID-19 vaccines. We present a case series of GBS reports submitted between February and November 2021 to our enhanced spontaneous surveillance system (SAEFVIC) in Victoria, Australia, following vaccination with either the adenovirus-vector vaccine Vaxzevria ChadOx1-S (AstraZeneca) or an mRNA vaccine (Comirnaty BNT162b2 [Pfizer-BioNTech] or Spikevax mRNA-1273 [Moderna]). For each report, Brighton Collaboration case definitions were used to describe diagnostic certainty. Severity was graded using the GBS Disability Score. The observed incidence of GBS following immunisation against COVID-19 was compared to expected background ICD10-AM G61.0 coded hospitalisations. There were 41 total cases of GBS reported to SAEFVIC following Vaxzevria (n = 38), Comirnaty (n = 3), or Spikevax (n = 0) vaccines. The observed GBS incidence rate exceeded the expected background rate for Vaxzevria only, with 1.85 reports per 100, 000 doses following dose 1, higher than the expected rate of 0.39 hospital admissions per 100, 000 adults within 42 days of vaccination. Of 38 GBS reports following Vaxzevria, the median age at vaccination was 66 years and median onset of symptoms was 14 days following immunisation. There was one death. Four cases initially categorised as GBS were later reclassified as acute-onset chronic inflammatory demyelinating polyneuropathy. Fatigue was the predominant persisting symptom reported at follow up. Additional global studies are required to characterise risk factors, clinical variability, and to provide precision and generalizability regarding AEFI risks such as GBS associated with different vaccine platforms, which will help inform communication of the potential benefits and risks of COVID19 vaccination.